THE COMPLEXITIES OF THE MEANING OF BHĀVANĀ AMONG THE BUDDHIST COMMUNITY: Case study in Janggleng hamlet, Tlogowungu, Kaloran, Temanggung - Suranto, Suranto; Widiyono, Widiyono (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2022)
Interpretation of the teaching of Buddhism occurs among Buddhists, especially Buddhists Monastery of Dharma Surya Janggleng. This phenomenon shows the complexity that exists among Buddhists. The study of complexity among Buddhist is important because it can see how far the development of Buddhists in understanding the teaching of Buddhism. Research on the complexity of the meaning of bhāvanā as an attempt to see the understanding of Buddhist in interpreting the teaching of Buddhism. Through the theory of complexity, phenomena and conditions of the community in Janggleng hamlet, Tlogowungu village. Based on the theory of complexity and social analysis with the theory of meaning construction system. It can be concluded that this study explains that there is a complex meaning of bhāvanā among Buddhists. This form of complexity can be seen from the meaning of bhāvanā which is interpreted as Tirakat, bhāvanā for inner calm and self-control, bhāvanā for peaceful life and health, and bhāvanā for attaining supranatural powers. This complexity is a part of the diversity of community understanding that can be a source of contextual knowledge.